2016
DOI: 10.21037/jtd.2016.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative survival for patients with thymoma complicating myasthenia gravis—preliminary retrospective results of the ChART database

Abstract: Background: It is so far not clear that how myasthenia gravis (MG) affected the prognosis of thymoma patients. The aim of this assay is to compare the postoperative survival between patients with thymoma only and those with both thymoma and MG. Methods:The Chinese Alliance for Research in Thymomas (ChART) registry recruited patients with thymoma from 18 centers over the country on an intention to treat basis from 1992 to 2012. Two groups were formed according to whether the patient complicated MG. Demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 7 publications
10
37
1
Order By: Relevance
“…Previous articles have reported that WHO classification, Masaoka stage, and R0 resection status may influence the recurrence and long‐term prognosis of thymomas . COX regression analysis in our study indicated that Masaoka stage III + IV, not‐R0 resection, and recurrence were independent risk prognostic factors, but older age seemed to be a protective factor for recurrence, which was similar to the study by Li .…”
Section: Discussionsupporting
confidence: 89%
“…Previous articles have reported that WHO classification, Masaoka stage, and R0 resection status may influence the recurrence and long‐term prognosis of thymomas . COX regression analysis in our study indicated that Masaoka stage III + IV, not‐R0 resection, and recurrence were independent risk prognostic factors, but older age seemed to be a protective factor for recurrence, which was similar to the study by Li .…”
Section: Discussionsupporting
confidence: 89%
“…In the ITMIG cohort, approximately one-third of patients with TETs had a PN/AI syndrome. 29 This is similar to the prevalence of MG reported in national retrospective database studies 29 , including Japanese Association for Research on the Thymus (JART) 30 , European Society of Thoracic Surgeons (ESTS) 31 , and Chinese Alliance for Research in Thymomas (ChART) 32 . There is overlap with these national databases and our ITMIG database cohort, including 31% cases from the ChART database and 14% cases from the ESTS database (Supplementary Data Fig.14), while the JART database was not included.…”
Section: Discussionsupporting
confidence: 74%
“…The prognostic value of MG associated thymoma remains controversial in the different reports of the literature, some established the presence of MG as a good survival prognostic factor related to the onset of MG symptoms that leads a prompt approach and treatment (23)(24)(25); others reported that having MG or not, didn't show any statistical significance, same as our results (11,(26)(27)(28); and finally, some studies reported even a worse prognosis in patients with MG (17,29). This discrepancies are probably due to the wide range of clinical and pathogenic variants in MG patients, the present study has several limitations: the information was retrospectively acquired at a single institution, it includes only 64 patients and a referral bias should be considered, nevertheless, this report is valuable because in the best of our knowledge there is scarce information about MG and thymoma from Hispanic referral cancer centers; a study from 1991 had one of the largest population with MG and thymoma, and they reported a better overall survival in patients with MG compared with TnMG group (30).…”
Section: Discussionmentioning
confidence: 99%